Strengthening Public and Private Accountability through Digital Forensic Accounting - Darwin, Khadijah (Sinergi International Journal of Accounting and Taxation, 2024)
This study presents a comprehensive narrative review on the evolution and application of forensic accounting in both public and private sectors within the context of digital transformation. It aims to analyze how the integration of forensic techniques with emerging technologies enhances fraud detection and prevention efforts. Utilizing a structured thematic analysis of current literature, the review synthesizes findings from multiple international contexts and disciplines, including auditing, governance, law, and data science. The analysis reveals that private organizations are leading in the adoption of technologies such as artificial intelligence, machine learning, and big data analytics for proactive fraud detection. In contrast, public sector institutions face challenges such as limited infrastructure, bureaucratic inertia, and slower technological uptake. Technological tools have significantly increased the accuracy and timeliness of forensic investigations, but their effectiveness is dependent on regulatory support, data integrity, and professional capacity. Discussion highlights the need for reform in forensic accounting education, standardized auditing procedures, and cross-sectoral collaboration. Recommendations include policy reforms to support digital auditing infrastructure and capacity building through interdisciplinary training. The study concludes that forensic accounting, when strategically integrated with governance and technology, becomes a vital tool in combating increasingly complex fraud schemes.